Policewomen who made history : breaking through the ranks - Snow, Robert L. (Rowman & Littlefield Publishers, 2010)
Beginning with a history of women in police work, Snow traces their rise through the ranks, focusing first on the first women to be given a patrol assignment. In their own words, policewomen describe the challenges and advantages of being a woman on the force, and demonstrate the perseverance many of them needed to make it in this mostly boys' club. Facing obstacles such as sex discrimination and harassment, requirements meant to block their ascent, and personal issues that arise when family members don'tunderstand their call to duty, these women broke new ground and paved the way for others w.